Pressure-varying CO2 distribution affects the ultrasonic velocities of synthetic sandstones. (July 2018) - Papageorgiou, Giorgos; Falcon-Suarez, Ismael; Chapman, Mark; Best, Angus
Abstract: We performed a novel experiment in which three synthetic sandstones – manufactured using a common method but having different porosities – were saturated with brine and progressively flooded with CO2 under constant confining pressure. The fluid pressure was varied around the critical pressure of CO2 and repeated measurements were made of resistivity, in order to assess the saturation, and elastic wave velocity during the flood. The measured saturated bulk moduli were higher than those predicted by the Gassmann–Wood theory, but were consistent with behaviour described by a recently derived poroelastic model which combines "patch" and "squirt" effects. Measurements on two of the samples followed a patch-based model while those on the highest porosity sample showed evidence of squirt-flow behaviour. Our analysis suggests that the appropriate fluid mixing law is pressure dependent, which is consistent with the notion that the effective patch size decreases as fluid pressure is increased. We derive simple empirical models for the patch dependence from fluid pressure which may be used in seismic modelling and interpretation exercises relevant to monitoring of CO2 injection.